Pengaruh Takaran Pupuk Guano dan Biochar terhadap Pertumbuhan dan Hasil Tanaman Kacang Merah (Phaseolus vulgaris L.) di Lahan Kering pada Dataran Menengah - Patrisius Naben; Krisantus Tri Pambudi Raharjo (Fakultas Pertanian, Universitas Timor, 2017)
Research carried out to know the effect of dosage of guano and biochar on growth and yield of red bean at middle plain dryland, in the experimental garden of the Faculty of Agriculture, Timor University from February to April 2017, using factorial Randomized Block Design 3 x 3 with 3 replication. The first factor is guano dosage consisting of 3 levels ie without guano, guano 5 t / ha and guano 10 t / ha, while the second factor is biochar dosage consisting of 3 levels ie without biochar, biochar 5 t / ha and biochar 10 t / ha. The results showed no interaction between guano and biochar applications. Guano 10 t / ha significantly increased soil moisture content (17.62%), leaf area (8,595 cm2), number of root nodules (175.11), root dry weight (0.70 g), root-canopy ratio (16.24), number of plant pods (2.86), number of seeds every pod (2.86), dry weight of seed (7.24 g) and seed weight every plot (1.17 t / ha) with yield increase percentage 31.1%. Increased levels of Biochar application did not show significant differences between treatment levels but tended to increase plant growth and yield.